2016
DOI: 10.5543/tkda.2016.55250
|View full text |Cite
|
Sign up to set email alerts
|

Cardioneuroablation in the treatment of neurally mediated reflex syncope: a review of the current literature

Abstract: Focused or extensive vagal ganglia ablation may be a potential alternative to pacemaker implantation in a carefully selected patient population. In contrast to pharmacological therapy and pacemaker implantation, ganglia ablation is designed to get to the root of the problem: disturbances in the intrinsic cardiac autonomic nervous system. This novel technique should be evaluated in large-scale, randomized, controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Previous reports demonstrated that CNA might be an alternative to permanent pacemaker in well selected patients with VVS [6,8] . Although short-term results after CNA are promising, ratio of positive response may be up to 23% of patients at post-procedural HUTs [8] . Since the type of positive response is not clearly indicated in the studies, there is no clinical data on what to do next.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports demonstrated that CNA might be an alternative to permanent pacemaker in well selected patients with VVS [6,8] . Although short-term results after CNA are promising, ratio of positive response may be up to 23% of patients at post-procedural HUTs [8] . Since the type of positive response is not clearly indicated in the studies, there is no clinical data on what to do next.…”
Section: Discussionmentioning
confidence: 98%
“…Although no need for additional equipment such as a stimulator with high-frequency stimulation feature or a software programme to convert local electrograms to spectral potentials seems to be the most important advantage of anatomical-based ablation, it was found to be related to higher RS recurrence rates in our recently published meta-analysis [4]. Also, an anatomical-based approach may increase the number of ablation points due to empirical ablation in the presumed sites.…”
mentioning
confidence: 86%
“…Four strategies have been used to map the GP and identify the ablation targets: high-frequency stimulation, purely anatomical localisation, atrial electrogram characteristics, and different combinations of these strategies [4]. In the anatomical approach, empirical ablation is performed in previously defined sites, on the basis of animal studies and human autopsy specimens.…”
mentioning
confidence: 99%
“…Radiofrequency ablation of ganglionic plexi in the right atrium, near the superior vena cava and sinus node, inferior vena cava, near the coronary sinus and AV node, and in the left atrium near the floor and near all four pulmonary veins with the aim of abolishing vagal efferent activation during VVS (cardioneuroablation) has shown promise in early observational studies, [69][70][71] but larger, controlled studies with long-term follow-up are needed to confirm the safety and efficacy of this procedure.…”
Section: Confounding Issuesmentioning
confidence: 99%